Image_2_Impact of the Invasive Beech Leaf-Mining Weevil, Orchestes fagi, on American Beech in Nova Scotia, Canada.tif - Jonathan D. Sweeney; Cory Hughes; Honghao Zhang; N. Kirk Hillier; Andrew Morrison; Rob Johns (2020)
The beech leaf-mining weevil, Orchestes fagi (L.), is native to Europe where it commonly attacks European beech. The weevil was discovered infesting American beech in Halifax and Cape Breton Island, Nova Scotia, Canada in 2012, but anecdotal reports of defoliated beech in the Halifax area as early as 2006 suggest it established 5–10 years prior to its discovery. Our objectives were to estimate the impact of O. fagi on American beech in forested sites and urban areas, as well as its economic impact on owners of residential properties with mature American beech. In 2014, we established fifteen plots in forested sites containing a total of 260 American beech at Sandy Lake, Oakfield, and Mount Uniacke (n = 5 plots per site), where weevil infestation levels were moderate, low, and nil, respectively. At the same time we recorded the degree of cankering by beech bark disease on the main stems of each tree. Plots were visited annually to record tree mortality (2014–2019) and percentage of leaves with larval mines or adult feeding (2016–2019). Between 2016 and 2019, the percentage of leaves mined by weevil larvae increased from 6 to 59% at Mount Uniacke and from 48 to 83% at Oakfield. During the same period, cumulative beech mortality increased from 35 to 48% at Mount Uniacke and from 10 to 70% at Oakfield. At Sandy Lake in 2016, 88% of the beech trees had died and there were too few living beech to collect a leaf sample in our plots so estimates of weevil damage (87% of leaves with mines) were obtained from life table plots in the same area. Tree mortality was associated with severity of cankering by beech bark disease only at Mount Uniacke, the site with the fewest years of defoliation by the leaf-mining weevil. We also surveyed residents of Halifax in 2016 and 2018 to determine the rate of beech mortality and costs of tree removal in urban residential areas in the same region (within 40 km) of the forest areas. Relative to the forested sites at Sandy lake and Oakfield, mortality rates were lower in urban areas (32% in ...